ANALISIS MODEL ALTMAN Z-SCORE DAN ZMIJEWSKI SEBAGAI METODE MEMPREDIKSI KONDISI KEBANGKRUTAN PADA PT. PAKUWON JATI TBK DAN PT. SENTUL CITY TBK PERIODE 2013-2022 - Cikal Calniva Izumi; Lily Setyawati Kristianti (Journal of Research and Publication Innovation, 2024)
This research aims to find out the level of bankruptcy at PT. Pakuwon Jati Tbk. And PT. Sentul City Tbk. The 2013-2022 period is based on the Altman Z-Score and Zmijewski method analysis. Researchers examined 2 (two) companies, namely PT. Pakuwon Jati Tbk. and PT. Sentul City Tbk. The research method used is quantitative descriptive method and secondary data collection. The population of this research is the Financial Report of PT. Pakuwon Jati Tbk. and PT. Sentul City Tbk. and the sample used in this research is a balance sheet and profit and loss report for 10 years from 2013-2022. Results of analysis of calculations using the Altman Z-Score method at PT. Pakuwon Jati Tbk. on average it is in the healthy zone and in 2015-2016 it is prone to bankruptcy. Analysis of calculations using the Altman Z-Score method at PT. Sentul City Tbk. on average it is in the bankruptcy-prone zone, in 2015 and 2020 it experienced bankruptcy. Analysis of calculations using the Zmijewski method at PT. Pakuwon Jati Tbk. and PT. Sentul City Tbk. is in the healthy zone every year.